Old Political Power in the New Government: Framing Analysis of Mainstream Media Sentiment toward the Indonesian House of Representatives - Nur Sofyan; Abi Pranaya Tyaswara; Akhmad Habibullah (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
The mass media has a constitutional obligation to act as a watchdog over power, but the reality of information circulation in Indonesia's current digital landscape demonstrates discursive inequality. This study aims to uncover the imbalance in mainstream media sentiment towards the performance of the House of Representatives of the Republic of Indonesia (DPR RI) and explain how the practice of omitting critical facts represents the success of the operation of information hegemony. This study uses a qualitative approach with a constructivist-critical paradigm. Data were collected through a purposive sampling technique on 127 news texts from national mainstream media portals published on July 8, 2025. The data analysis process was carried out systematically through thematic coding, Robert N. Entman Framing Analysis, and critical analysis of the detection of missing facts in the field. The findings indicate a dominant positive sentiment of 90.5% regarding the performance of the DPR RI. Through framing analysis, mainstream media are proven to carry out exclusion mechanisms by omitting critical facts. National mainstream media institutions have experienced a decline in their oversight function and have shifted to being an amplification instrument that distributes the interests of elite hegemony. This inequality is driven by the structural relationship between media conglomerates and political elites, which limits the independence of newsrooms. This study recommends evaluating regulations on cross-media ownership and improving civil society's political literacy to create a deliberative public sphere.